Pengaruh Brand Image, Brand Experience dan Influencer Marketing Terhadap Keputusan Pembelian Konsumen Melalui Minat Beli Sebagai Variabel Intervening Pada Produk Kecantikan Scarlett Whitening - Tri Harto Katamso; Sugianto Sugianto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research was conducted with the aim of showing the influence of brand image, brand experience and influencer marketing on purchasing decisions with the purchase interest variable being the intervening variable. This study uses a quantitative approach. The research population is Scarlett Whitening consumers in Jakarta, the total of which is not known for certain. Sampling used purposive sampling technique and obtained 90 samples. The data analysis technique uses path analysis. The research results show that brand image has no influence on purchasing decisions. Brand image also has no influence on purchasing interest. Brand experience has a significant positive influence on purchasing decisions and purchasing interest. Influencer marketing variables have no influence on purchasing decisions. Influencer marketing influences purchasing interest. Then the purchase interest variable has no influence on purchasing decisions. Meanwhile, the results of research on mediation (intervening) variable tests produce that brand image, brand experience and influencer marketing have an influence through purchasing interest on purchasing decisions. This research can be used by companies in deciding policies and developing strategies in maintaining a good brand image from consumer perception, and using brand experience and influencer marketing to promote products.